2008
DOI: 10.2193/2007-273
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Lethal, Directed Wolf‐Depredation Control in Minnesota

Abstract: : Wolf (Canis lupus) depredations on livestock in Minnesota, USA, are an economic problem for many livestock producers, and depredating wolves are lethally controlled. We sought to determine the effectiveness of lethal control through the analysis of data from 923 government‐verified wolf depredations from 1979 to 1998. We analyzed the data by 1) assessing the correlations between the number of wolves killed in response to depredations with number of depredations the following year at state and local levels, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 11 publications
2
38
1
1
Order By: Relevance
“… 1 Allen and Sparkes (); 2 Anderson et al (); 3 Azevedo and Murray (); 4 Bagchi and Mishra (); 5 Van Bommel et al (); 6 Bradley and Pletscher (); 7 Breck et al (); 8 Espuno et al (); 9 Gula (); 10 Gusset et al (); 11 Harper et al (); 12 Herfindal et al (); 13 Huygens et al (); 14 Iliopoulos et al (); 15 Karanth et al (); 16 Kolowski and Holekamp (); 17 Van Liere et al (); 18 Mech et al (); 19 Michalski et al (); 20 Odden et al (); 21 Odden et al (); 22 Ogada et al (); 23 Sagor et al (); 24 Stahl et al (); 25 Stahl et al (); 26 Stander (); 27 Suryawanshi et al (); 28 Treves et al (); 29 Tumenta et al (); 30 Valeix et al (); 31 Wilson et al (); 32 Woodroffe et al (); 33 Woodroffe et al (); 34 Zarco‐González et al ().…”
Section: Resultsmentioning
confidence: 99%
“… 1 Allen and Sparkes (); 2 Anderson et al (); 3 Azevedo and Murray (); 4 Bagchi and Mishra (); 5 Van Bommel et al (); 6 Bradley and Pletscher (); 7 Breck et al (); 8 Espuno et al (); 9 Gula (); 10 Gusset et al (); 11 Harper et al (); 12 Herfindal et al (); 13 Huygens et al (); 14 Iliopoulos et al (); 15 Karanth et al (); 16 Kolowski and Holekamp (); 17 Van Liere et al (); 18 Mech et al (); 19 Michalski et al (); 20 Odden et al (); 21 Odden et al (); 22 Ogada et al (); 23 Sagor et al (); 24 Stahl et al (); 25 Stahl et al (); 26 Stander (); 27 Suryawanshi et al (); 28 Treves et al (); 29 Tumenta et al (); 30 Valeix et al (); 31 Wilson et al (); 32 Woodroffe et al (); 33 Woodroffe et al (); 34 Zarco‐González et al ().…”
Section: Resultsmentioning
confidence: 99%
“…We used data on mass and color of wolves older than 1 year live-trapped for a radio-tracking study in northern Cook, Lake, and St. Louis counties from 1968 to 2006 (Mech 2009) and captured for a US Department of Agriculture Wildlife Services depredation-control program from 1975 through 2006 (Fritts 1982;Harper et al 2005Harper et al , 2008 in Lake, St. Louis, Koochiching, Itasca, Lake-of-the-woods, Beltrami, Clearwater, Kittson, Roseau, Marshall, Polk, Pennington, and Red Lake counties, arranging the data point for each county or group of counties centrally across the northern Minnesota map (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…If non‐depredating packs dissolve in response to harvest, surviving or colonizing wolves may begin to prey on livestock (Bjorge and Gunson ). In addition, studies reported lethal removal, particularly of entire packs, reduced the likelihood of future predation events on livestock locally (Bjorge and Gunson , Bradley et al ) but not population‐wide (Harper et al ). Frequent turnover of packs may therefore affect conflicts with livestock depending on the frequency of pack replacement (Bradley et al ) and individual traits of wolves recolonizing vacant territories (Bjorge and Gunson ).…”
mentioning
confidence: 99%